When are Students Ready for Research Methods? A Curriculum Mapping Argument for the Political Science Major. Issue 2 (3rd April 2017) - Bergbower, Matthew L.
ABSTRACT: For many political science programs, research methods courses are a fundamental component of the recommended undergraduate curriculum. However, instructors and students often see these courses as the most challenging. This study explores when it is most appropriate for political science majors to enroll and pass a research methods course. The hypothesis posits that the number of prior introductory-level political science courses can be a strong precursor to research methods success, even for those who are upper-class students and majors. This hypothesis is tested by analyzing data from six sections of an undergraduate research course offered at a midsized public university. The results demonstrate that students are most likely to succeed in their research methods course if they are majors with at least five previous political sciences courses completed. Recommendations for course prerequisites and specific curriculum mapping are offered in light of these findings.